Communication and Intercultural Dialogues: a Peruvian case study - Pedraglio, Santiago (2017)
Nearly 500 years ago, the “Cajamarca encounter” between the Spanish conquerors and the Inca Atahualpa symbolized the lack of communication Peru was founded on. This event decisively conditioned the power structure during colonial times and even later in the republic. However, during this prolonged period, many indigenous and Afro-descendants Peruvian cultures, subordinate and marginalized, have experienced dissimilar processes of intercultural communication. There is a growing back and forth flow of communication between cultures considered subordinate and hegemonic. There also are  multiple contacts between indigenous cultures and in-between these and others, such as the Afro-descendant. This process of communication –and, simultaneously, affirmation of cultural identities– has gained a new impetus: it unfolds vigorously in rural areas and in cities. Moreover, cultural identities have ceased to exclusively identify with vernacular languages. The State has incorporated some of this; nevertheless, much remains to be done.